Biased perceptions of income distribution and preferences for redistribution: Evidence from a survey experiment - Guillermo Cruces; Ricardo Perez Truglia; Martin Tetaz (Institute for the Study of Labor (IZA), 2011)
Individual perceptions of income distribution play a vital role in political economy and public finance models, yet there is little evidence regarding their origins or accuracy. This study examines how individuals form these perceptions and posits that systematic biases arise from the extrapolation of information extracted from reference groups. A tailored household survey provides original evidence on the significant biases in individuals' evaluations of their own relative position in the distribution. Furthermore, the data supports the hypothesis that the selection process into the reference groups is the source of those biases. Finally, this study also assesses the practical relevance of these biases by examining their impact on attitudes towards redistributive policies. An experimental design incorporated into the survey provides consistent information on the own ranking within the income distribution to a randomly selected group of respondents. Confronting agents' biased perceptions with this information has a significant effect on their stated preferences for redistribution. Those who had overestimated their relative position and thought of themselves relatively richer than they were demand higher levels of redistribution when informed of their true ranking. This relationship between biased perceptions and political attitudes provides an alternative explanation for the relatively low degree of redistribution observed in modern democracies.
urn:nbn:de:101:1-201105173359
Keywords: D31; D83; H24; H53; I30; 330; perceptions of income distribution; limited information; preferences for redistribution; field experiment